1986
DOI: 10.1136/oem.43.7.490
|View full text |Cite
|
Sign up to set email alerts
|

Joint effect of occupation and nationality on the prevalence of peptic ulcer in German workers.

Abstract: In Central Europe and in South Africa duodenal ulcer disease has been reported to occur twice as often in migrant workers as in the indigenous population. To investigate the reasons for this phenomenon the joint effect of occupation and nationality on the prevalence of gastric and duodenal ulcer was studied in a survey of 73 000 active members of the German workforce. Non-ulcer dyspepsia and gastric, but not duodenal, ulcer were found more frequently in migrant than in indigenous workers. Manual workers were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…But Sonnenberg and Haas have reported higher incidence of gastric and duodenal ulcer and non-ulcer dyspepsia among manual labourers in German population. 9 Majority of our subjects were non vegetarians (83%), but no relation was found between diet and dyspeptic symptoms. Similar results were also obtained in a case control study by Cuperus et al 10 Another case control study from Norway by Lind et al concluded that abdominal symptoms were due to food hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…But Sonnenberg and Haas have reported higher incidence of gastric and duodenal ulcer and non-ulcer dyspepsia among manual labourers in German population. 9 Majority of our subjects were non vegetarians (83%), but no relation was found between diet and dyspeptic symptoms. Similar results were also obtained in a case control study by Cuperus et al 10 Another case control study from Norway by Lind et al concluded that abdominal symptoms were due to food hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the high prevalence among migrant workers reflects their current predominance in physically demanding jobs, and that the secular decline in incidence of peptic ulcer may be linked to a progressive reduction in average energy expenditures at work [44].…”
Section: Occupational Activitymentioning
confidence: 99%
“…It is now recognised that those deprived in childhood (for example living with poor sanitation or family overcrowding) have the highest H. pylori infection risk. [11][12][13][14][15][16] As socio-economic conditions improved in Western societies in the 20th century, so too the prevalence and mortality of PUD declined, with changes related to the period of birth. [17][18][19][20] The declining numbers of operations observed in York in successive decades suggests this too is a birth cohort effect.…”
Section: The Decline In Psmentioning
confidence: 99%